PENGARUH KOMITMEN, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI KECAMATAN PASANGKAYU KABUPATEN MAMUJU UTARA (Study Kasus pada SMA Negeri 1 Pasangkayu dan MA DDI Pasangkayu) - Ningsih, Prapti (Katalogis, 2016)
This research intends to find out and analyze the influence of commitment, competency, and work environment on teachers’ performance in Districk of Mamuju Regency (case study in SMAN Pasangkayu and MA DDI Pasangkayu). Population in this study consists 41 teachers’as civil servants. The research employs multiple linear regressions analysis to explain the influence of independent variables towards dependent variable, both simultaneously and partially. Hypothesis test is conducted on significant level  α≤0,05 by using SPSS 16. The test results show that commitment, competency, and work environment simultaneously have positive and significant influence on teachers performance with the adjusted R2 of 0,825 or 82,5%. The remaining is explained by other variables that are not studied. Commitment positively and significantly influences teachers’ performances with regression coefficient of 0,051 with sig. 0,003; competency positively and significantly influences teachers’ performances with regression coefficient of 0,650 with sig. 0,000; work environment positively and significantly influences teachers’ performances with regression coefficient of 0,282 with sig 0,000.